Walking – a technical-strategic resource: propositions for planning left-hand movement on the guitar (Orfeu, 2025)
This paper discusses one of the steps in the application of a technical-strategic resource in formulation, walking. walkingis a left-handed behavior on the guitar, which can be defined as the succession of movements that makes it possible to sustain the sound between the notes, asuccession of intentions.The steps involved in applying the resource are planning or organizing the practice, training and evaluation, the first of which is the subject of this paper. Performance planning is understood as the systematization of the practice, a context in which the decoding of the musical text makes it possible to segment it into parts that can be practiced using systems and/or methods of progressive parts. When segmenting, it is recommended to consider which components (movements) of the left-hand action on the guitar are independent and which are grouped together as interdependent, thus avoiding the isolated practice of movements that would be better performed if practiced together. The practical applications of these propositions will be illustrated through a description of the planning of the left-hand movement in an excerpt from Luis Milán’s Pavan II(1536). Preliminary results point to the possible application of the guidelines proposed here, as well as further research.
Keywords: walking; classical guitar technique; performance planning; practice strategy; segmentation